A Water-Borne Tularemia Outbreak Caused by Francisella tularensis subspecies halorctica in Central Anatolia Region - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2011)
In this study, we investigated a waterborne tularemia outbreak occured in Kadiozu, a village of Cerkes county of Cankiri province (located in North-west part of central Anatolia, Turkey) between 18 November 2009-24 December 2009. Active surveillance was conducted to determine clinical characteristics and risk factors of cases after two patients from the same village had been diagnosed as oropharyngeal tularemia. All villagers were examined, and clinical specimens from cases and water samples which may be the source of outbreak in the field investigations were taken. Cases were in the form of oropharyngeal, glandular and pneumonic. Polymerase chain reaction (PCR) and cultures were conducted from lymph node aspirates, throat swabs taken from cases and samples from water sources of epidemic zone. All serum samples taken from the villagers were screened for F.tularensis antibodies with micro-agglutination test (MAT). Oropharyngeal tularemia was diagnosed in 11 patients, glandular form in 3 patients and pneumonic form in one patient according to clinical and laboratory results. Age of the patients ranged between 6-75 years old (mean age: 52.5 years) and thirty one of them (54.7%) were female. MAT titers ranged between 1/160 and 1/5120 in cases of tularemia. Causative agent was grown in the cultures of two patients (including a throat swab and a lymph node aspirate). F.tularensis DNA was shown by PCR in a throat swab and four lymph node aspirates. F.tularensis was also detected by PCR in the water sample obtained from one of the spring water commonly used by villagers. Only one of the lymph node samples obtained from two different patients, was positive by direct fluorescent antibody method. Causative agent was defined as F.tularensis subsp. holarctica by conventional and also molecular methods. Patients were treated with aminoglycoside (streptomycin, gentamicin, amikacin) or quinolone (ciprofloxacin, levofloxacin) antibiotics. Treatment failure was observed in five patients, due to the delay in initiating treatment. Comparison of characteristics and risk factors for tularemia cases versus controls yielded age and contact with rodent excreta at home as potential risk factors (p = 0.001 and 0.002, respectively). The epidemic was controlled after cleaning the tank collecting spring water and chlorination of the water. Tularemia which is an emerging disease in Turkey is spreading to non-endemic regions and represent a significant threat for public health.
Keywords: Tularemia; Francisella tularensis subspecies holarctica; outbreak; culture; PCR; DFA; Turkey; TURKEY; STRAINS